2000
DOI: 10.1016/s0960-9822(99)00277-8
|View full text |Cite
|
Sign up to set email alerts
|

A conserved motif in Crumbs is required for E-cadherin localisation and zonula adherens formation in Drosophila

Abstract: We propose a model in which the interaction of the Crumbs carboxyl terminus with Discs Lost organises a membrane-associated protein complex in the apical cytocortex of epithelial cells. This scaffold mediates the localisation and stabilisation of the zonula adherens component DE-cadherin, a crucial component for the maintenance of epithelial cell polarity and tissue integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
241
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(260 citation statements)
references
References 42 publications
(77 reference statements)
14
241
1
2
Order By: Relevance
“…The Sdt-dPATJ-CRB complex is localized to a distinct domain apical to the zonula adherens in the Drosophila epithelial cells called the subapical region. It is widely accepted that the Sdt-dPATJ-CRB complex regulates the formation of the Drosophila zonula adherens and E-cadherin localization (Grawe et al, 1996;Tepass, 1996;Klebes and Knust, 2000), although how the protein complex interacts with components of the zonula adherens remains unclear (Knust and Bossinger, 2002). The observations in our study suggest that this mechanism is conserved, and PALS1 regulates the formation of adherens junctions in mammalian epithelial cells in addition to its role in tight junction formation.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The Sdt-dPATJ-CRB complex is localized to a distinct domain apical to the zonula adherens in the Drosophila epithelial cells called the subapical region. It is widely accepted that the Sdt-dPATJ-CRB complex regulates the formation of the Drosophila zonula adherens and E-cadherin localization (Grawe et al, 1996;Tepass, 1996;Klebes and Knust, 2000), although how the protein complex interacts with components of the zonula adherens remains unclear (Knust and Bossinger, 2002). The observations in our study suggest that this mechanism is conserved, and PALS1 regulates the formation of adherens junctions in mammalian epithelial cells in addition to its role in tight junction formation.…”
Section: Discussionsupporting
confidence: 51%
“…However, the subapical region is not the site of the intercellular seal in Drosophila cells, which instead reside below the zonula adherens in the septate junction. In Drosophila, the Sdt-dPATJ-CRB complex regulates the formation of the zonula adherens and E-cadherin localization (Grawe et al, 1996;Tepass, 1996;Klebes and Knust, 2000), although how this protein complex interacts with components of the zonula adherens remains unclear (Knust and Bossinger, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Drosophila and cultured mammalian epithelial cells showed that PATJ associates with Sdt/Pals1, which, in turn, binds to the transmembrane protein Crb, which targets the complex to TJs in vertebrates and the corresponding subapical region in Drosophila (20,42).…”
Section: Patj Is Recruited By Sdt To a Complex With Baz At The Apicalmentioning
confidence: 99%
“…La perte d'expression de Crumbs a pour conséquence un défaut de fusion des jonctions adhérentes au niveau de la zonula adherens (ZA), autour du pôle apical des cellules épithéliales de l'ectoderme [8], ce qui entraîne une perte de polarité et la mort des cellules épithéliales par apoptose [7,9]. Deux régions du domaine cytoplasmique de la protéine sont cruciales pour sa fonction dans les cellules des épithéliums primaires [10,11]; ces deux régions étant conservées de la drosophile à l'homme, il est probable que la protéine humaine est également impliquée dans le développement ou le maintien de la polarité cellulaire. Les deux motifs de Crumbs impliqués dans l'organisation des zonula adherens et des épithéliums sont les quatre derniers acides aminés, ERLI, et les acides aminés entourant la tyrosine (Y) proche du domaine transmembranaire ( Figure 2B).…”
Section: Crb Et Drosophileunclassified
“…Elle est en particulier requise pour l'organisation du cytosquelette contenant une spectrine apicale sous-membranaire [18], la β heavy -spectrine, qui forme des tétramères avec l'α-spectrine. Cette interaction pourrait être indirecte, via une interaction entre Crumbs et la D-moesine, un membre de la famille des protéines ERM (ezrine/radixine/moesine) [18] liant l'actine aux protéines membranaires et reconnaissant une séquence, présente dans le domaine cytoplasmique de Crumbs, indispensable à sa fonction [11]. Crumbs se situe donc au centre d'un réseau d'interactions entre des protéines d'assemblage de complexes, comme Sdt et D-PATJ, et des protéines directement liées au cytosquelette d'actine, ce qui permettrait de contrôler l'organisation de la zone marginale et la morphogenèse épithéliale [19,20].…”
Section: Crb Et Drosophileunclassified